2018
DOI: 10.1016/j.celrep.2018.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Selective NaV1.7 Antagonists with Long Residence Time Show Improved Efficacy against Inflammatory and Neuropathic Pain

Abstract: Selective block of Na1.7 promises to produce non-narcotic analgesic activity without motor or cognitive impairment. Several Na1.7-selective blockers have been reported, but efficacy in animal pain models required high multiples of the IC for channel block. Here, we report a target engagement assay using transgenic mice that has enabled the development of a second generation of selective Nav1.7 inhibitors that show robust analgesic activity in inflammatory and neuropathic pain models at low multiples of the IC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 41 publications
(71 reference statements)
1
85
0
Order By: Relevance
“…1B and 5E, fig. S6, and Movie 1) (50)(51)(52)54). AaH2 embraces a highly conserved PM glycan on the VSD4-Na v PaS channel ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B and 5E, fig. S6, and Movie 1) (50)(51)(52)54). AaH2 embraces a highly conserved PM glycan on the VSD4-Na v PaS channel ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is unclear to what degree Na v 1.7 must be inhibited, or what population of Na v 1.7 channels must be inhibited, to induce an analgesic effect. 24,37 Lastly, it remains to be seen if a lifelong absence and the temporary deactivation of Na v 1.7 result in comparable phenotypes. 38 For an imaging agent, some of the above-mentioned translational hurdles do not apply, because imaging agents should not elicit a pharmacological response.…”
Section: Discussionmentioning
confidence: 99%
“…1B), recently failed in patients suffering from painful diabetic neuropathy 34 , which led Pfizer to stop further development activities. Bankar et al suggested this failure possibly reflected insufficient Na V 1.7 targeting in the clinical study and recommend the evaluation of acyl-sulfonamides with better physiochemical and pharmacological properties 35 , including a longer residence time on the target 36 . Since PF-05089771 is intentionally peripherally restricted, compounds with improved blood brain barrier (BBB) penetrability in humans, might better engage NaV1.7 channels expressed close to or on the bouton of dorsal root ganglion (DRG) neuron dorsal horn synapse.…”
Section: Introductionmentioning
confidence: 99%